2020
DOI: 10.1088/1755-1315/452/1/012095
|View full text |Cite
|
Sign up to set email alerts
|

Investigating community adaptability and resilience in Urban Kampung, study case: Water and sanitation infrastructure of Kampung Muka, North Jakarta

Abstract: Urban kampung is an urban settlement with a community that indicates the characteristics of “vulnerability” and adaptability at the same time. The vulnerabilities of their existence rely from internal and external pressures which consist of chronic stresses (the community’s limitations to fulfil their daily needs) and acute shocks (sudden threats that emerges from outside the community). Simultaneously their vulnerabilities are strengthened by community-based adaptations as a respond of kampung residents towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…While studies did not explicitly reference these models or use their terminology, we found adaptation stakeholders commonly taking steps throughout all phases. For example, studies reported steps in the exploration phase to identify performance gaps and the need for adaptation (43,67,85), in the preparation phase to prepare the adapted intervention materials (19,20,48), in the implementation phase to pilot test and refine the adapted intervention (18,44), and in the sustainment phase to evaluate the adapted intervention (56,66). Most studies focused on the early stages of assessment and preparation to identify adaptation needs and propose solutions.…”
Section: Updates and Refinements To Prior Adaptation Modelsmentioning
confidence: 99%
“…While studies did not explicitly reference these models or use their terminology, we found adaptation stakeholders commonly taking steps throughout all phases. For example, studies reported steps in the exploration phase to identify performance gaps and the need for adaptation (43,67,85), in the preparation phase to prepare the adapted intervention materials (19,20,48), in the implementation phase to pilot test and refine the adapted intervention (18,44), and in the sustainment phase to evaluate the adapted intervention (56,66). Most studies focused on the early stages of assessment and preparation to identify adaptation needs and propose solutions.…”
Section: Updates and Refinements To Prior Adaptation Modelsmentioning
confidence: 99%